Tradisi Pembacaan Yasin 41 Studi Living Qur’an - Tia Subu Simamora & Hasiah & Sawaluddin Siregar (IAIN Padangsidimpuan, 2021)
This research is the tradition of reading Yasin 41 which is carried out by the community of Paran Gadung village, Padang Bolak Julu district, Padang Lawas Utara district. This practice is carried out if someone is seriously ill, then Yasin 41 reads it with the hope that after reading the sick person back to health or if there is no hope of recovery, his death will be made easier. The formulation of the problem in this study is how the implementation systematics, as well as the community's interpretation of the Yasin 41 reading tradition.The aim is to find out the steps for implementing the Yasin 41 tradition and to find out the meaning of the Paran Gadung village community regarding the Yasin 41 reading tradition. which uses collection techniques by means of observation, interviewing, and documentation and uses books related to the study of living Qur'an and Hadis by Sahiron Syamsudin. The method used in this research is descriptive. The conclusion of this study is that the process of implementing Yasin 41 must be accompanied by a supervisor who already understands its implementation and several verses that are read repeatedly, then the community's consumption of the implementation of the Yasin 41 reading tradition is to get closer to oneself. to Allah SWT, the form of personality as a social being, and the last is to expect blessings from Alla SWT.